China: Regaining Growth Momentum after the Pandemic - Ligang Song; Yixiao Zhou (ANU Press, 2024)
The slower growth of the Chinese economy in the aftermath of the pandemic has prompted the Chinese Government to adopt measures to boost domestic consumption and deepen structural reform, with the effectiveness of such policies beginning to be felt. However, China still faces challenges that will affect its growth dynamics down the track. These include the slowdown of its real estate sector, the complex internal and external environments for macroeconomic policy, the high level of income inequality, weak growth in investment by the private sector, negative population growth, high levels of debt, deglobalisation, weakness in the financial sector and equity markets, the inadequacy of its fiscal system and the imperative to decarbonise the economy. China must confront these challenges to maintain growth momentum and achieve higher levels of income and living standards. The theme of the 2024 China Update book is China: Regaining Growth Momentum after the Pandemic. It discusses some of the challenges and policy issues that are being watched with keen interest by decision-makers and markets alike, including: What are the obstacles to economic growth in the aftermath of the pandemic and how can these be overcome? What are the key challenges and opportunities for China to move to the next level of development against the backdrop of negative population growth? Is it time for a Tax-Sharing System Reform 2.0 to consolidate China's fiscal position? What are the challenges facing China's small and medium enterprises? How is China's business environment faring, and what are the implications for investment? How does China's urban housing affordability impact its low fertility rate? How will the trade conflict between China and the United States play out regarding semiconductors and other high-tech products? How does China–Africa bilateral agricultural trade impact on African rural transformation?
Keywords: 330; Chinese Economy; Chinese Government; economic growth; population growth